Diamond-like carbon coatings for moulding - Toh, Wei Quan (2014)
Diamond-Like Carbon (DLC) thin film coatings are a novel type of Carbon materials. Their unique properties such as low coefficient of friction combined with high wear resistance have allowed them to find applications in modern industries. One application is in the field of molding process.